Political Participation of Beginner Voters in the 2020 Regional Head Election in Binjai City - M. Faisal Husna (IHSA Institute, 2022)
The level of political participation of beginners is worth knowing, given that the votes of novice voters can determine in an election, especially in the election of the Mayor of Binjai. All citizens of the city have the right to participate in the excitement of the mayoral election provided that they meet the requirements as novice voters in the election. Currently, the age of students in eleven (11) and twelve (12) high schools, whose age ranges from seventeen (17) to eighteen (18) years, has entered the category of novice voters in the mayoral election in accordance with the rules in Law (UU) No.1 of 2015 concerning the Stipulation of Government Regulations in Lieu of Law No.1 of 2014 concerning the Election of Governors, Regents and Mayors, become Laws. Beginner voters become the target of election contestants, both from political parties and personal, including their supporters. Beginner voters are highly influenced and will make other friends. A high sense of participation encourages novice voters to consider a necessity in voting in the General Election or Pilkada. This is their reason because it will be the first experience in their life in the people's democratic party